2022
DOI: 10.3390/v14050976
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a Carbohydrate-Binding Module Therapy, Neumifil, against SARS-CoV-2 Disease in a Hamster Model of Infection

Abstract: The rapid global spread of severe acute respiratory coronavirus 2 (SARS-CoV-2) has resulted in an urgent effort to find efficacious therapeutics. Broad-spectrum therapies which could be used for other respiratory pathogens confer advantages, as do those based on targeting host cells that are not prone to the development of resistance by the pathogen. We tested an intranasally delivered carbohydrate-binding module (CBM) therapy, termed Neumifil, which is based on a CBM that has previously been shown to offer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The use of different SARS-CoV-2 strains will also likely lead to variation in transmission efficiency, as reported for different variants in the hamster model [ 9 , 20 ]. Despite the limitations in the number of recipient animals becoming infected being lower than expected, the data presented within demonstrated that Neumifil exerts a significant reduction in clinical progression in a natural disease model, providing additional evidence to previous work which showed a positive effect after direct intranasal challenge [ 14 ]. Whilst this study was designed to test Neumifil administered as a combination of prophylactic and therapeutic uses, further experiments are warranted to ascertain timings and relevance for antiviral treatment initiation.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The use of different SARS-CoV-2 strains will also likely lead to variation in transmission efficiency, as reported for different variants in the hamster model [ 9 , 20 ]. Despite the limitations in the number of recipient animals becoming infected being lower than expected, the data presented within demonstrated that Neumifil exerts a significant reduction in clinical progression in a natural disease model, providing additional evidence to previous work which showed a positive effect after direct intranasal challenge [ 14 ]. Whilst this study was designed to test Neumifil administered as a combination of prophylactic and therapeutic uses, further experiments are warranted to ascertain timings and relevance for antiviral treatment initiation.…”
Section: Discussionsupporting
confidence: 64%
“…We have previously reported that Neumifil confers protective effects against an intranasal challenge inoculum of SARS-CoV-2 in the Syrian hamster preclinical model [ 14 ]. Within this report, we have assessed the natural transmission model in the context of antiviral agent testing.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to different limits of the detection of the assays, with histological and RNAscope assessment being limited to a small area of a tissue section, whereas RT-PCR was performed on a larger homogenised sample section. This observation was also highlighted in the analysis of SARS-CoV-2 viral RNA from challenged hamsters [ 43 ]. Another plausible explanation is that the RNAscope probe used here targets only the positive-sense RNA observed during virus replication [ 20 ].…”
Section: Discussionmentioning
confidence: 79%